Antecedents of Taxpayers Compliance: Evidence from Central Java - Nurul Aulia Dewi; Arya Samudra Mahardhika (Agregat: Jurnal Ekonomi dan Bisnis, 2021)
The study aimed to analyze the effect of Motivation, Awareness and Service Quality to Taxpayers Compliance at KPP Pratama Kebumen. The research method used descriptive statistics using primary data obtained by distributing online questionnaires in the form of google form to individual taxpayers registered at KPP Pratama Kebumen. The analysis method used in this research is multiple linear regression using SPSS 24 for Windows. The results of the coefficient of determination (R2) are the value of Adjusted R Square of 54.8% which indicates that taxpayers’ compliance is influenced by the variables of Motivation, Awareness and Service Quality. The results of this study indicate that motivation has a significant effect in a positive direction on taxpayer compliance, while awareness and service quality had no effect on taxpayer compliance.